Fiqh Study on Bank Interest and Its Development - Fitra Ardiansyah; Syifa Pajastia; Khairil Alfi Syahri (Jurnal Cendikia ISNU SU, 2025)
Bank interest is a controversial issue in the study of Islamic jurisprudence, especially in the context of the development of the modern banking system which makes it the main mechanism in conventional economic activities. The majority of classical fiqh scholars view bank interest as a form of riba that is prohibited because it contains additional elements of the principal of the loan that has the potential to cause injustice and exploitation, as affirmed in the Qur'an and hadith. However, some contemporary scholars offer a more contextual approach by taking into account the principles of emergency, benefits, and global economic realities. This study aims to analyze the legal position of bank interest in the perspective of Islamic jurisprudence and examine the development of ijtihad of classical and contemporary scholars in responding to conventional banking practices. The research method used is qualitative research with a literature study approach, through the study of classical fiqh sources, the thoughts of contemporary scholars, and literature related to Islamic economics and finance. The results of the study show that there are different views among scholars regarding the law of bank interest, which reflects the dynamics of ijtihad in responding to changes in the modern economic system. The majority of scholars still prohibit bank interest because of its similarity to riba, while some contemporary scholars provide limited space of abilities on the condition that they are not exploitative and intended for benefit. In conclusion, the fiqh study of bank interest emphasizes the importance of a comprehensive and contextual understanding of sharia principles in modern economic practice, as well as the need to strengthen the Islamic financial system as a fair alternative and in accordance with Islamic values.